Electrodeposition of CuGaSe2 Layer from Solutions with Different Complexing Agents - Sang, Ngo Dinh; Quang, Pham Hong; Tu, Le Tuan (Communications in Physics, 2011)
CuGaSe_2 (CGS) thin films were deposited on ITO substrates by electrodeposition from the solutions with different acidic agents, namely hydrochloric, sulphamic and citric acids. Cyclic voltammetry (CV) studies of unitary Cu, Ga, and Se systems and ternary Cu-Ga-Se systems were carried out to determine the reduction potentials, the mechanism of deposition and the ability to deposit of each constituent. The reduction peaks were observed in all unitary systems except the case of Ga from solution with non-acid and citric acid. For the ternary systems, the voltammograms only show the peaks relating to the reduction of Cu^2 + and Se^4 + , indicating the difficulty in deposition of Ga. The electrodepositions have been processed at - 0.6 V and - 0.95 V vs. SCE. The concentration of the films was determined by EDS. For all complexing agents, the concentration of Ga has been found to depend strongly on the deposition potential and has reached to the value of about 16% at. at potential of -0.95 V from the solutions with hydrochloric and sulphamic acids.